Direct evidence for a substantive reaction between the Criegee intermediate, CH2OO, and the water vapour dimer1. Issue 7 (21st February 2015) - Lewis, Tom R.; Blitz, Mark A.; Heard, Dwayne E.; Seakins, Paul W.
<x xml:space="preserve">Abstract</x> The C1 Criegee intermediate, CH2OO, reaction with water vapour has been studied.